2013
DOI: 10.1186/bcr3436
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances reveal IL-8 signaling as a potential key to targeting breast cancer stem cells

Abstract: Breast cancer stem-like cells (CSCs) are an important therapeutic target as they are purported to be responsible for tumor initiation, maintenance, metastases, and disease recurrence. Interleukin-8 (IL-8) is upregulated in breast cancer compared with normal breast tissue and is associated with poor prognosis. IL-8 is reported to promote breast cancer progression by increasing cell invasion, angiogenesis, and metastases and is upregulated in HER2-positive cancers. Recently, we and others have established that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 99 publications
(122 reference statements)
8
157
0
2
Order By: Relevance
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…To determine aberrantly expressed genes in MDS and AML stem and progenitor cells, we previously conducted a parallel transcriptional study comparing LT-HSCs, ST-HSCs, and GMPs from AML samples with deletion of chromosome 7 (27) to healthy control counterparts 10 ( Figure 1A). A small set of 7 genes was found to be consistently overexpressed in all compartments (LT-HSCs, ST-HSCs, and GMPs) and included IL8.…”
Section: Il8 Is Overexpressed In Mds and Aml Hscs And Progenitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Already known to enhance tumor cell growth and promote angiogenesis (5,6), more recently, IL8 has been proposed to be a potent protumoral factor. In breast cancer and in glioblastoma, it has recently been suggested that IL8 directly favors cancer stem cells (7,8).…”
Section: Introductionmentioning
confidence: 99%